Assessment of Lip Competence and its Relation to (sagittal molar relationship and overjet): A Retrospective Analysis - Muhialdeen, Taban Ibrahim (Journal of Neonatal Surgery, 2025)
One of the most important opportunities of orthodontic treatment is to improve the aesthetic and morphological harmony as well as the function of the oral and maxillofacial regions. Achieving lip competency is a critical goal in orthodontic treatment, as it contributes to both dental and facial aesthetics by positively influencing the soft tissue profile, particularly the nasolabial angle and the positioning of the upper and lower lips. The aim of this study is to assess lip competency and find out the relationship between lip competency with molar relationship and overjet. Materials and methods: This retrospective study was conducted at the College of Dentistry/ Hawler Medical University. A total of 362 patients, aged between 16 and 47, were involved in the study. The samples were obtained from patients attending the orthodontic department of the College of Dentistry. The patient records were reviewed and analyzed, encompassing age, gender, lip competency, angle classification and overjet. A P-value of ≤ 0.05 was deemed statistically significant. Results: The majority of the sample was found to have competent lips (80.9%), while incompetent lips were present in (19.1%) of the sample. Most of the samples exhibit Class I malocclusion (66.3%), followed by Class II (24%), and then Class III (9.7%). Normal overjet is the most frequent, representing (67.1%) of the sample, while increased overjet is the second most frequent, accounting for (22.9%) of the sample. Conclusion: lip competence was found to be highly significantly associated with molar relationship and overjet